Qual a importância do tamanho dos predadores e da predação sobre recrutas para a organização de comunidades incrustantes marinhas? - Oricchio, Felipe Theocharides [UNIFESP] (2015)
Predation represents a strong factor able to shape the richness of species, composition and relative abundance in marine communities. However, the size of predators, their feed preferences, preys vulnerability and development stage and recruitment composition must affect predation effects over community organization. Therefore, the present study aimed to understand how the size of predators, the moment of the community development in which predation occurs and the differential recruitment patterns affect the dynamics and structure of marine fouling community. To do so, we developed two experiments at Yacht Club Ilhabela (YCI), at Ilha Bela, SP. The first controlled the size of the predators which access benthic communities developed in PVC plates, through exclusion cages with to different meshes. And a second experiment fully replicated three times, quantifying the intensity and composition of recruitment and the survivorship of recruits, when exposed or protected from predators, in two different sites at YCI: the breakwater and inside the YCI. The breakwater presents similar condition to coastal regions surrounding the YCI while inside the turbulence is reduced but sedimentation and concentration of pollutants are high. Thereby, this study also described how costal constructions change the fouling community organization. Our results confirm the predation as a strong force shaping community dynamics and structure, changing community composition but not species richness. Small predators only affect the free space after one month, delaying the colonizing process. Ascidian’s recruits are the main target of predators, regardless the size of the predator, and their removal in the beginning of colonization reduces space monopolization by this good competitors. Therefore, predation alters the hierarchical relationships among community components, facilitating the occurrence of bryozoans. The composition and abundance of recruits as well as changes in predation pressure between marina’s sites influenced community dynamics. Recruitment of bryozoans, mainly Schizoporella errata, was higher inside the YCI than in the breakwater, where serpulids and ascidians recruits, mainly Didemnum perlucidum, were abundant. Such differences in recruitment patterns were diminished by high levels of predation on ascidians at the breakwater. Community structure changed over space and time, so that during the first temporal replica, predation affected the community structure at both sites. At the second temporal replica, predation did not affect predation, regardless of site and at third experimental cycle, predation affects the community organization only at the breakwater. Yet, when predation had effects over community organization, it facilitated the occurrence of bryozoans by removing ascidian species. Sporadic recruitment peaks of some species, such as Herdmania pallida, also had long-term effects on the community organization, in a way that community structure after three months depended on the initial recruitment. Thereby, we demonstrated that predation effects over community organization cannot be generalized, varying over time, sometimes due to different recruitment patterns. We demonstrated as well that temporal unreplicated experiments may lead to false generalizations and that costal constructions can change both, recruitment patterns and predation pressure and, therefore, may affect marine costal diversity.